Analysis of Menstrual Knowledge and Mother-Child Communication on Anxiety 4TH-6TH Grades Female Students at Ash-Shodiq Islamic Elementary School Bululawang in 2024 - Mukti Wibowo, Kusnanto; Dwi Anjani, Ikrima; Supriyadi, Supriyadi; Dwi Tama , Tika (Jurnal Health Sains, 2026)
Menarche, the onset of menstruation, is a significant event in a woman’s life, yet it often becomes a source of anxiety for adolescent girls, especially those lacking adequate knowledge and support. This study aimed to analyze the influence of menstrual knowledge and mother-child communication on anxiety levels in fourth to sixth grades female students at Ash-Shodiq Islamic Elementary School Bululawang. This study employing a cross-sectional design with a descriptive analytical quantitative approach, with involved 55 selected through purposive sampling. The results revealed that majority of students experienced severe anxiety related to menstruation. Ordinal logistic regression analysis revealed poor menstrual knowledge and poor effective mother-child communication significantly contributed to elevated anxiety levels in partially. However, through simultaneously analysis, it was found that only menstrual knowledge had a significant effect on anxiety after controlling for the mother-child communication variable. These findings underscore the importance of sound menstrual knowledge in mitigating anxiety in students facing menarche, while effective mother-child communication also plays a crucial role, albeit one that needs to be complemented by adequate knowledge.